Substructural Logic: a unifying framework for second generation datamining algorithms - de Haas, Erik; Adriaans, Pieter (Proceedings of the Amsterdam Colloquium, 1999)
In this paper we propose a framework for data mining algorithms based on a system of substructural logic. We show the connections between data mining, inductive logic programming and grammar induction. Furthermore we present a small familiy of substructural logics that can represent modern comples information systems. This small family of substructural logics on its turn will facilitate the design of efficient datamining algorithms using techniques from the field of inductive logic programming.